In-situ syntheses of graft copolymers by metal-free strategies: combination of photoATRP and ROP - Gorkem Yilmaz (Designed Monomers and Polymers, 2020)
A completely metal-free and environmentally friendly strategy is demonstrated for the preparation of graft copolymers by combining photoinduced Atom Transfer Radical Polymerization (ATRP) and Ring Opening Polymerization (ROP). Polymerizations are simultaneously realized in a one-pot manner. For this purpose, bare vinyl monomers, vinyl monomers with hydroxyl functional groups, and lactone monomers were simultaneously polymerized under visible light using specific catalysts. While vinyl monomers construct the main chain, the lactone monomers were polymerized from the hydroxyl functions present at the side chain. Spectral and chromatographic analyses prove that the utilized strategy is successful in the preparation of graft copolymers controlled molecular weights and narrow distributions.